ANALYSIS OF THE NEED TO REFORM THE SOLIDARITY ASSOCIATIONS LAW AND THE ASSOCIATIONS LAW IN COMPLIANCE WITH THE UN SUSTAINABLE DEVELOPMENT GOALS - Ruiz Jiménez, Kendall (2025)
In Costa Rica, there is a regulation for non-profit organizations such as civil associations and solidarity associations, but to what extent does their regulation comply with the UN Sustainable Development Objectives? Although the statutes are true of each organization of this nature establish specific treatments according to the purposes it pursues, it must also be reviewed whether, due to its nature alone, that its primary purpose is not profit, the obligation to establish purposes for the construction of a more sustainable society is regulated or, failing that, if a reform is necessary to comply with these objectives.